Srikandi of the Ministry of Religious Affairs: Women’s Leadership in PTKIN Confronting Patriarchal Culture - Valensius Ngardi; Ferdi Yufriadi; Sahrul Sori Alom Harahap; Tri Wibowo; Musnif Istiqomah (Pascasarjana UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This study investigates the role of female leaders, referred to as the